(untitled) (Journal of Social Sciences Review, 2023)
Bullying is a widespread phenomenon that affects individuals of all ages and backgrounds. With the advancement of technology, cyber bullying has also become a growing concern among young people. The purpose of this research project is to examine the effects and consequences of bullying on youth and students, with a particular focus on Pakistan. The research aims to identify the reasons for bullying, its prevalence, and its impact on individuals, families, and society as a whole. The study uses a quantitative research methodology to gather data and analyze the findings. The research reveals that bullying is a common problem among school and college students in Pakistan, with a significant number of individuals reporting being victims of bullying at least once in their life. The most common forms of bullying reported are verbal and emotional abuse. The study also highlights the role of parental involvement, moral education, and the availability of safe spaces for young people in preventing bullying atmosphere. In extreme cases, bullying can even lead to suicide, as the victim may feel helpless and isolated. The research suggests that a combination of measures, including moral education, legislation, and strict laws, can help prevent bullying in Pakistan.